Arc and resistance welding and tumours of the endocrine glands: a Swedish case-control study with focus on extremely low frequency magnetic fields. Issue 5 (18th April 2005) - Håkansson, N; Stenlund, C; Gustavsson, P; Johansen, C; Floderus, B
Abstract : Background: Mechanisms for potential effects of extremely low frequency (ELF) magnetic fields on carcinogenesis have not been identified. A potential pathway could be an interaction with the endocrine system. Aims: To analyse occupational exposure to ELF magnetic fields from welding, and tumours of the endocrine glands. Methods: This case-control study was based on a cohort with an increased prevalence of high exposed individuals. A total of 174 incident cases of tumours of the endocrine glands, 1985–94, were identified and data were obtained from 140 (80%) of these cases; 1692 controls frequency matched on sex and age were selected, and information on 1306 (77%) individuals was obtained. A short questionnaire was sent to a work administrator at the workplaces of the cases and controls. The exposure assessment was based on questions about job tasks, exposure to different types of welding, and exposure to solvents. Results: There was an overall increased risk for all tumours of the endocrine glands for individuals who had been welding sometime during the follow up. The increased risk was attributable to arc welding; for resistance welding there was no clear evidence of an association. We found an increased risk for the adrenal glands in relation to arc welding, and for the parathyroid glands in relation to both arc welding and resistance welding. An imprecise increase in risk was also noted for tumours of the pituitary gland for arc welding. No confounding effect was found for solvent exposure, and there was no sign of biological interaction. Conclusion: The increased risks of endocrine gland tumours related to welding might be explained by exposure to high levels of ELF magnetic fields.